2013
DOI: 10.1167/iovs.12-11268
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment for the Ability of Cirrus, RTVue, and 3D-OCT to Diagnose Glaucoma

Abstract: PURPOSE. We compared the ability of circumpapillary retinal nerve fiber layer (cpRNFL) thickness and macular parameters obtained by three spectral-domain optical coherence tomography (SD-OCT) instruments to detect glaucoma. METHODS.We enrolled 87 normal eyes and 145 glaucomatous eyes (75 early glaucomatous eyes (EGs), mean deviation > À6 dB). Each participant was imaged using Cirrus, RTVue, and 3D-OCT to evaluate the average and quadrant cpRNFL thicknesses. The macular retinal nerve fiber layer (mRNFL), gangli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 23 publications
2
56
0
2
Order By: Relevance
“…Cirrus RNFL thickness measurements detected significant differences between healthy and glaucomatous eyes, which confirm previous reports using SD-OCT [31][32][33] but also using TD-OCT. [34][35][36] Most Cirrus measurements also detected significant differences between healthy and glaucoma suspect eyes, except in the temporal and nasal regions of RNFL thickness measurements.…”
Section: Discussionsupporting
confidence: 90%
“…Cirrus RNFL thickness measurements detected significant differences between healthy and glaucomatous eyes, which confirm previous reports using SD-OCT [31][32][33] but also using TD-OCT. [34][35][36] Most Cirrus measurements also detected significant differences between healthy and glaucoma suspect eyes, except in the temporal and nasal regions of RNFL thickness measurements.…”
Section: Discussionsupporting
confidence: 90%
“…[14][15][16] The optic nerve and neural rim can be examined with imaging technology to quantify the degree of structural damage; the association between image-based measurements of neural rim and RNFL loss and VF damage is well recognised [17][18][19][20][21] and the spatial relationship between the structural damage and VF loss has been established. 13,22 Imaging-based quantitative measurements have diagnostic utility [23][24][25][26][27][28][29] and numerous publications support the ability of imaging-based measurements to identify glaucoma deterioration. [30][31][32][33][34][35][36][37][38][39][40] Progressive structural change has been shown to be useful as a predictor of subsequent VF loss.…”
Section: Trial Registrationmentioning
confidence: 99%
“…2 Recent studies showed that the ability of the macular GCIPL parameters to diagnose glaucoma is comparable with that of the peripapillaryretinal nerve fiber layer (pRNFL) and optic nerve head parameters. [3][4][5][6][7][8] Because of the characteristic distribution of the retinal nerve fiber axons in the retina, asymmetric visual field defects often occur between the superior and inferior hemifields. Mikelberg and Drance 9 found that 70% of eyes had initial damage limited to a single hemifield and 57% still had only a single hemifield defect at the completion of follow-up.…”
mentioning
confidence: 99%